ASYMPTOTICS OF THE NORMING CONSTANTS OF THE STURM–LIOUVILLE PROBLEM - Harutyunyan, T.N. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
We derive new asymptotic formulae for the norming constants of Sturm– Liouville problem, which generalize and make more precise previously known formulae, by taking into account the smooth dependence of norming constants on boundary conditions.